Modern trabecular metal-backed glenoid components in total shoulder arthroplasty: What is the evidence? A systematic review. (February 2021) - Malahias, Michael-Alexander; Chytas, Dimitrios; Kostretzis, Lazaros; Trellopoulos, Angelos; Brilakis, Emmanouil; Antonogiannakis, Emmanouil
Background: A number of papers have been published reporting on the clinical performance of modern trabecular metal-backed glenoid components in total shoulder arthroplasty. However, no systematic review of the literature has been published to date. Methods: The US National Library of Medicine (PubMed/MEDLINE), and the Cochrane Database of Systematic Reviews and EMBASE were queried for publications from January 1980 to October 2019 utilizing keywords pertinent to total shoulder arthroplasty, trabecular metal, and clinical outcomes. Results: Overall, seven articles were included for analysis (322 operated shoulders, mean follow-up range: 2–4 years). The survival rate of modern trabecular metal-backed glenoid components was 96% (309 out of 322 cases) at 43 months mean follow-up, while the rate of aseptic loosening was 0.3% (1 out of 322 cases). There were 35 cases (10.9%) with glenoid component radiolucency (one of them required revision), and 37 cases (11.5%) of metal debris formation, with four of them undergoing revision. Conclusions: There was low quality evidence to show that the use of modern trabecular metal-backed glenoid components in total shoulder arthroplasty may be safe and effective at short-term follow-up. However, this analysis showed alarmingly high rates of both radiolucency of the glenoid component and metal debris formation which raise concern for potential failure of this glenoid component in the long term. Therefore, we feel that modern trabecular metal-backed glenoid components should be still used with caution as part of a structured surveillance or research program until we know if there is a detriment to the prosthesis in the medium to long term. Level: Systematic review, IV.